Weighting Facial Features Extraction using Geometric Average - Saparudin (Computer Engineering and Applications Journal (ComEngApp), 2017)
Human facial feature extraction is an important process in the face recognition system. The quality of the results from the extraction of human facial features is determined by the degree of accuracy. The weighting of human facial features is used to test the accuracy of the methods used. This research produces the process of weighting the facial features automatically. The results obtained are the same as those seen by the human eyes. Â